PENGARUH BUDAYA PATRIARKI TERHADAP PERCERAIAN DALAM MASYARAKAT HINDU BALI - I Wayan Ferry Suryanata (Belom Bahadat, 2022)
Patriarchal culture is a habit that places the position of men more dominant than women. Men have more influence and power than woman. Woman in this case are poitioned as weak, helpless an do not have enough power to equalize position in a family or society. The continuous application of patriarchal culture can trigger divorce. Because if a man considers himself the most powerful and everything must be according to his will, then it is possible that the husband and wife relationship will experience a divorce. In such conditions, of course a woman wil experience mental torment and in the can not stand the unequal treatment. Moreover, in Balinese Hindu society, the role of women as wives should not be underestimated. Where their role greatly affects the lives of their families and community groups. For example, in ritual ceremonies, the role of women is needed to make offerings or offerings. Because in general the only women who can make offerings are women and not all Balinese women understand the problem of burdensomeness. While the position of Balinese women in the family and society is considered lower. It is clear in literature that women must be respected and loved so that the family lives happily and does not experience destruction.